Design Science Guided Sports Information System Framework Development for Sports Data Analytics - Nimmagadda, Shastri; Mullins, Antony; Reiners, Torsten; Mani, Neel (Association for Information Systems, 2020)
We identify various sports-related challenges pertinent to teams, player selections, and event management. We examine both technical and managerial decisions made during player promotion, and various factors influenced the matches. We conceptualize that the game strategies, player and team selections, performance-based sports ecology management entities can blend into an informatics paradigm for which sports data modelling and analytics are required. In addition, reviews of players in social media have significance in weighing the economic value of players. With a motivation to systematize and franchise the branded teams and players to generate revenues, we aim at articulating a logical Sports Information System (SIS), for which various design-science guided artefacts are proposed. The research evaluates game strategies, the promotion of promising players, team-based performance, and economic indicators. Documentation of sports facts and logical storage models are vital to generate metadata and assess how players performed and what factors can motivate future matches.